ANALISIS PENERAPAN AKUNTASI SUMBER DAYA MANUSIA PADA RSUP DR. MOHAMMAD HOESIN PALEMBANG - Icha Fauziah; Aspahani Aspahani; Emylia Yuniartie (AKUNTABILITAS, 2013)
The research aims to determine the capitalization of cost of human resources on RSUP financial statements. Dr. Mohammad Hoesin Palembang and his influence. The type of research to be done is case studies on the company. Data analysis methods use a deskriftive analysis. Based on the results of research and analysis conducted on the collected data it can be concluded that the treatment of costs associated with the cost of human resources as a burden is immediately eliminated in the period of occurrence resulting in the lack of information that was submitted so as to make the management not know exactly how far the achievement of hospital objectives has been achieved economically. In drafting the financial statement of RSUP Dr. Mohammad Hoesin using conventional accounting which refers to the government accounting standards (SAP) and the nonprofit hospital accounting guidelines where the unfounded investment in human resources is Conducted by hospitals, expenditures for human resources i.e. spending on human resource development are recognised as burdens.